2011
DOI: 10.1002/anie.201101882
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Sensing Device for the Discrimination of Proteins Based on Manganese‐Doped ZnS Quantum Dots

Abstract: Lab-on-a-nanoparticle: the triple-channel optical properties of Mn-doped ZnS quantum dots (fluorescence, phosphorescence, and light scattering) are explored to develop a multidimensional sensing device for the discrimination of proteins in a lab-on-a-nanoparticle approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
136
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(137 citation statements)
references
References 57 publications
0
136
1
Order By: Relevance
“…These new spectral properties are quite different from those of pure PEI and most of the MnÀZnS nanoparticles. [13,14] Pure PEI did not show any absorption in the range of l = 250-700 nm and only exhibited one very weak emission for band G (Figure 1 B), whereas most MnÀ ZnS nanoparticles only displayed the band-edge absorption of ZnS at about l = 300 nm, and simultaneously excited PL bands at about l = 450 and 590 nm. [8, 14f] The new absorption at l % 365 nm and the individually excited PL band G of PEI/MnÀ ZnS nanocomposites can be ascribed to the CT complex of PEI and Zn/Mn.…”
Section: Synthesis and Characterization Of Pei/mnàzns Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…These new spectral properties are quite different from those of pure PEI and most of the MnÀZnS nanoparticles. [13,14] Pure PEI did not show any absorption in the range of l = 250-700 nm and only exhibited one very weak emission for band G (Figure 1 B), whereas most MnÀ ZnS nanoparticles only displayed the band-edge absorption of ZnS at about l = 300 nm, and simultaneously excited PL bands at about l = 450 and 590 nm. [8, 14f] The new absorption at l % 365 nm and the individually excited PL band G of PEI/MnÀ ZnS nanocomposites can be ascribed to the CT complex of PEI and Zn/Mn.…”
Section: Synthesis and Characterization Of Pei/mnàzns Nanocompositesmentioning
confidence: 99%
“…A 1 ), which was incorporated into the ZnS host lattice (Figure 1 B). [13,14] Owing to the presence of PEI with abundant amino groups, the PEI/MnÀZnS nanocomposite was highly water soluble and exhibited good acidic stability, [12a,b] even at pH 3.0-5.0 ( Figure S3 in the Supporting Information). In addition, the PL properties of the PEI/ MnÀZnS nanocomposite could be adjusted by controlling the feed ratio of PEI/Zn (Figure 2 A) as a result of the super capabilities of PEI to coordinate with metals.…”
Section: Synthesis and Characterization Of Pei/mnàzns Nanocompositesmentioning
confidence: 99%
“…Liu et al [88] established a dual-channel sensor by the changes of conductivity and emission of CL during catalytic reaction of VOCs on nano-SnO 2 . Wu et al [89] simultaneously utilized the optical properties of Mn-doped ZnS QDs to develop a triple-channel sensor for the discrimination of eight proteins in a "lab-on-a-nanoparticle" mode. The multidimensional sensor is even able to identify the target protein in complex sample matrix, showing good application prospects.…”
Section: Sensorsmentioning
confidence: 99%
“…[10]. Some authors, for instance, have shown their potential biological applications in fluorescent biolabeling [14] and biosensing [15,16]. In this work, we present optimized ZnSe nanoparticles obtained as result of a chemometric assay applied to a simple colloidal route for the synthesis of water-dispersed Mndoped ZnSe QDs aiming at high intensity d-d emission for biolabeling purposes.…”
Section: Introductionmentioning
confidence: 98%